5 Effect of remote ischaemic preconditioning on coronary artery function in patients with stable coronary artery disease. (25th January 2018) - Corcoran, David S; Young, Robin; Cialdella, MD Pio; McCartney, Peter; Bajrangee, Amrit; Hennigan, Barry; Collison, Damien; Carrick, David; Shaukat, Aadil; Good, Richard; Watkins, Stuart; McEntegart, Margaret; et al.
Abstract : Background: Remote ischaemic preconditioning (RIPC) is a cardioprotective intervention invoking intermittent ischaemia in a tissue remote from the heart. Its mechanisms are incompletely understood. We hypothesised that RIPC might enhance coronary vasodilatation by an endothelium-dependent mechanism. Methods: We performed a prospective, randomised, sham-controlled, blinded clinical trial. Patients with stable coronary artery disease undergoing elective angiography were randomised 1:1 to RIPC or sham. Endothelial-dependent and –independent function was assessed with intracoronary (ic) acetylcholine (ACh) and ic nitrate, respectively. Coronary luminal diameter was assessed by QCA. Primary outcome: between-group difference in mean% change in coronary luminal diameter following ACh. Results: Following angiography, 60/75 patients (mean ±SD age 57.5±8.5 years; 80% male) were eligible and completed the protocol (n=30 RIPC, n=30 sham). The mean% change in coronary luminal diameter was −13.3±22.3% and −2.0±17.2% in the sham and RIPC groups respectively (difference 11.32%, 95% CI: 1.2 to 21.4, p=0.032) (figure 1). This remained significant with age and sex as covariates (difference 11.01%, 1.01–21.0, p=0.035). Conclusions: RIPC attenuates the extent of vasoconstriction induced by intracoronary acetylcholine infusion, and this endothelium-dependent mechanism may contribute to its cardioprotective effects.